نظرية التقادم وتطبيقاتها في التشريع الجنائي -الحدود أنموذجا - دراسة مقارنة بين الفقه الإسلامي والتشريع الجزائي الجزائري - براهمي, عبد الكريم (University of eloued جامعة الوادي, 2014)
تناول هذا البحث نظرية التقادم وتطبيقاتها في التشريع الجنائي، واقتصر على الحدود كأنموذج، وذل بالدراسة المقارنة بين الشريعة ا سلامية والقانون الجزائي الجزائري؛ وهذا من خلال ذكر أقوال الفقها التي انقسمت إلى ثلاثة أقوال، كان الراجح منها رأي الجمهور القاضي بعدم تقادم الجرائم الحدية مطلقا، وذل خلافا لما هو عليه في القانون؛ حيث جا هذا البحث في فصلين وتحت كل فصل مبحثان؛ وقد خصص الفصل الأول للحديث عن أحكام التقادم، وذل من حيث المفهوم، ونطاق السريان، وأساسه الذي يستند إليه، وكذا العوارض التي تطرأ عليه، بينما عني الفصل الثاني بالحديث عن تقادم الجرائم والعقوبات، وعرض نماذج تطبيقية لتقادم الحدود الشرعية، وأخرى لتقادم الجرائم والعقوبات في القانون الجزائي الجزائري والآثارالمترتبة على كل منهما This research confines the Theory of Prescription and its application on the Criminal Code taking into consideration Alhodoud as an example model, where a comparison is raised between the Islamic and Algerian penal legislation. Consequently, the Islamic jurists (Fuqahā) views, in this case, have been divided into three, and what is considered true is the audience’s opinion which interpreted the absolute of non-prescription of Alhodoud This research divided into two crimes unlike what’s provided in the law. chapters. Under each chapter there were two topics. However, the first chapter points out to the provisions of Prescription regarding its definition, effectiveness, and what it relies on, in addition to what it takes issue of. Whereas the second chapter discusses the Prescription of crimes and punishments, some examples of prescription of Alhodoud in Islam and Algerian penal legislation as well as the implications which occur upon both of them.
شريعة وقانون
Keywords: الحدود/نظرية التقادم/التشريع الجنائي; Frontiers / statute of limitations / criminal legislation